2010
DOI: 10.1016/j.ajog.2009.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence, and natural history of simple ovarian cysts among women >55 years old in a large cancer screening trial

Abstract: Objective-To measure the occurrence and natural history of simple ovarian cysts in a cohort of older women.Study Design-Simple cysts were ascertained among a cohort of 15,735 women from the intervention arm of the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial, through 4 years of transvaginal ultrasound screening.Results-Simple cysts were seen in 14% of women the first time their ovaries were visualized. The one-year incidence of new simple cysts was 8%. Among ovaries with one simple cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 23 publications
2
36
0
1
Order By: Relevance
“…65 Although 12% of women had morphologic change develop, there were no invasive ovarian cancers identified that were attributable to the identified index unilocular cyst. Moreover, an 8 -12% annual incidence of new simple cysts was documented among postmenopausal women, and this is consistent with other published data.…”
Section: Postmenopausal Populationmentioning
confidence: 95%
See 2 more Smart Citations
“…65 Although 12% of women had morphologic change develop, there were no invasive ovarian cancers identified that were attributable to the identified index unilocular cyst. Moreover, an 8 -12% annual incidence of new simple cysts was documented among postmenopausal women, and this is consistent with other published data.…”
Section: Postmenopausal Populationmentioning
confidence: 95%
“…9,10,66 -68 Further lending support to this theory are cohort and large prospective observational studies that indicate the removal of persistent simple ovarian cysts is not associated with a decrease in the proportion of expected deaths from ovarian cancer relative to other cancers, 69 and that monitoring of patients with unilocular ovarian cysts smaller than 10 cm without intervention is not associated with evidence of malignant transformation over the course of prolonged observation. [61][62][63][64][65] Thus, the present literature indicates that it may not always be necessary to surgically remove asymptomatic unilocular ovarian cysts thought to represent benign entities. Further, it implies that the purpose of a follow-up protocol in this setting is to capture prevalent ovarian cancer that may have been missed by imperfectly sensitive index diagnostic imaging studies, rather than that of monitoring for benign processes that may transform into malignant.…”
Section: Low-risk Adnexal Mass (No Surgical Intervention)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian cancer screening trials [3][4][5][6][7] have provided valuable information concerning the relationship between tumor morphology and risk of malignancy. Likewise, serum biomarker patterns 8,9 and analysis of tumor blood flow 10,11 have been shown to be useful in selected cases.…”
mentioning
confidence: 99%
“…Simple ovarian cysts as large as 3 cm have been reported in as many as 15% of postmenopausal patients; most such cysts spontaneously regress, as verified at serial US examinations (35,70,71). The simple cyst seen at imaging in early menopause probably represents an occasional ovulatory event or an atretic follicle.…”
Section: Postmenopausal Life Stagementioning
confidence: 90%